1994
DOI: 10.1515/znc-1994-1-209
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization and Peroxidizing Phytotoxicity of Thiadiazolidine Herbicides

Abstract: Certain 5-(arylimino)-3,4-tetramethylene-1,3,4-thiadiazolidin-2-ones (thiadiazolidines) are peroxidizing bleaching herbicides which interrupt chlorophyll biosynthesis, inhibit the activity of protoporphyrinogen oxidase, lead to accumulation of protoporphyrin IX, and induce ethane formation in the light. The same effects are caused by their isomers, the 4-aryl-1,2-tetramethylene-l,2,4-triazolidin-3-one-5-thiones (triazolidines). Couples of thiadiazolidines and corresponding triazolidine isomers were synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The isomerisation in vivo of the isourazole proherbicide fluthiacet‐methyl (Appeal ® , 1999; Kumiai Chemical Industry Co., Ltd, Tokyo, Japan) in the plant by glutathione S ‐transferase (GST) resulted in the urazole derivative (Fig. ), which gives strong and selective post‐emergence herbicidal control of annual broadleaf weeds in cotton (10–15 g AI ha −1 ) and in maize/corn, turf and soybeans (5–10 g AI ha −1 ) …”
Section: Proherbicides For Weed Controlmentioning
confidence: 99%
“…The isomerisation in vivo of the isourazole proherbicide fluthiacet‐methyl (Appeal ® , 1999; Kumiai Chemical Industry Co., Ltd, Tokyo, Japan) in the plant by glutathione S ‐transferase (GST) resulted in the urazole derivative (Fig. ), which gives strong and selective post‐emergence herbicidal control of annual broadleaf weeds in cotton (10–15 g AI ha −1 ) and in maize/corn, turf and soybeans (5–10 g AI ha −1 ) …”
Section: Proherbicides For Weed Controlmentioning
confidence: 99%
“…It is stable towards hydrolysis. Fluthiacet-methyl is produced by reaction of 1-[(2-fluoro-4-chloro-5-thiomethylacetate)phenylthiocarbamoyl]-2-methoxycarbonylhexahydropyridazine with methanolic potassium hydroxide, followed by treatment with trichloromethyl chloroformate [455].…”
Section: Flurochloridonementioning
confidence: 99%
“…A similar tendency was observed with both the triazolidinediones (2, 5, 9, 12 and 15) and triazolidine-dithiones (4, 7, 11, 14 and 17). The order of Protox inhibition among the triazolidin-one-thiones, triazolidine-diones and triazolidine-dithiones is as follows: tetramethylene analogues (12, 13 and 14) > trimethylene analogues (9, 10 and 11) > pentamethylene analogues (15,16 It has been reported that maximum length and width of peroxidizing herbicides match closely with the full-length and one-half width of the protoporphyrinogen-IX molecule.18' 19) So, our objective was to find out a relationship between Protox inhibition and steric parameters, maximum length (L) and maximum width (W) between the N1-and N2-substituent in the most stable conformation (see Fig. 2), with respect to our triazolidin-onethione compounds (1, 3, 6, 8, 10, 13 and 16 n stands for number of data, r the correlation coefficient, s the standard deviation, respectively.…”
Section: Molecular Orbital Calculationsmentioning
confidence: 99%